Word Formation Processes in Children's Literature: L. Frank Baum’s Novel Wonderful Wizard of Oz (1900) and Its Animation Movie Produced by Little Fox Youtube Channel (2021) - Bunga Indahyani; Leni Marlina (Universitas Negeri Padang, 2023)
This research discussed about types of word formation processes in children’s literature in The Wonderful Wizard of Oz novel and its animation movie. This research used the word formation theory proposed by Yule (2010) to find out the types of word formation in The Wonderful Wizard of Oz novel and its animation movie. This research was the descriptive qualitative method. The data were all sentences containing word formation in the selected chapters studied in the novel and animation movie of The Wonderful Wizard of Oz. The findings showed that there were 64 data contained word formation in novel and animation movie. In the novel found 35 data which are word formation, they are blending (1 data), borrowing (9 data), compounding (12 data), clipping (1 data), and derivation (12 data). Children's literature in the novel The Wonderful Wizard of Oz uses half types of word formation, there are five types of word formation out of ten types of word formation. Meanwhile, in the animation movie found 29 data which are word formation, they are back-formation (1 data), blending (1 data), borrowing (1 data), compounding (10 data), derivation (15 data), and multiple process (1 data). Children's literature works in animation movie used more than half the types of word formation, there are six of the ten types of word formation. The researcher concluded that compounding and derivation is the word formation process mostly used in novel, whereas in animation movie the most word formation process used is derivation.